THE ROLE OF DIGITAL LITERACY IN THE DEVELOPMENT OF 21ST-CENTURY SKILLS IN STUDENTS - Ummi Rasyidah; Ethan Tan; Nong Chai (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
The integration of digital technologies in education has become a critical factor in shaping the skills required for success in the 21st century. Digital literacy, defined as the ability to effectively navigate, evaluate, and create information using digital tools, is increasingly seen as an essential skill in fostering cognitive and social competencies. This study explores the role of digital literacy in the development of 21st-century skills, including critical thinking, creativity, communication, and collaboration, in students. The research aims to investigate how digital literacy influences students' ability to develop these competencies and identify specific digital tools that facilitate this process. A mixed-methods approach was employed, combining surveys, digital literacy assessments, and interviews with educators and students. The results indicate that students with higher digital literacy levels demonstrate significantly better performance in creativity (75%) and critical thinking (68%), as well as improved collaboration and communication skills. The study concludes that digital literacy plays a pivotal role in equipping students with the necessary skills to navigate complex problems, communicate effectively, and collaborate in diverse environments. The research suggests that integrating digital literacy into educational curricula is crucial for preparing students for future challenges and opportunities.